PENERAPAN AKUNTANSI SYARIAH PADA AKAD MURABAHAH DAN MUDHARABAH DI LEMBAGA KEUANGAN SYARIAH - RUSLAN JAYADI (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2024)
This study aims to analyze the application of sharia accounting in murabahah and mudharabah contracts in sharia financial institutions based on PSAK 102 and PSAK 105. Murabahah is a sale and purchase contract with a profit margin, while mudharabah is a cooperation contract between the fund owner and the fund manager with a profit sharing system. This study uses a qualitative descriptive approach through literature studies and analysis of financial report documents from several sharia financial institutions. The results of the study indicate that the application of PSAK 102 and PSAK 105 is quite consistent, although there are challenges in terms of risk recognition and transparency of profit sharing in mudharabah contracts. Improvement of the accounting information system and HR training is needed to support accountability in recording sharia-based transactions.